2022
DOI: 10.3389/fpsyg.2022.761956
|View full text |Cite
|
Sign up to set email alerts
|

Police Decision-Making in the Absence of Evidence-Based Guidelines: Assessment of Alcohol-Intoxicated Eyewitnesses

Abstract: Regarding police procedures with alcohol-intoxicated witnesses, Swedish police officers have previously reported inconsistent and subjective decisions when interviewing these potentially vulnerable witnesses. Most officers have also highlighted the need for national policy guidelines aiding in conducting investigative interviews with intoxicated witnesses. The aims of the two studies presented here were to investigate whether (1) police officers’ inconsistent interview decisions are attributable to a lack of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…To date, interrogators and interviewers must use their own judgment when deciding how to conduct interrogations with intoxicated persons as the research on alcohol/drugs and cognition in the legal context is still limited. Furthermore, many countries lack evidence-based guidelines for interviews with intoxicated and substance using persons (see Evans et al, 2009 ; Crossland et al, 2018 ; Monds et al, 2021 ; Hagsand et al, 2022a , b ; Pettersson et al, 2022 ). As the first novel study on interrogations concerning low-stakes crimes related to alcohol and/or drugs, the present study provides useful information about current Swedish interrogation practices and areas for improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, interrogators and interviewers must use their own judgment when deciding how to conduct interrogations with intoxicated persons as the research on alcohol/drugs and cognition in the legal context is still limited. Furthermore, many countries lack evidence-based guidelines for interviews with intoxicated and substance using persons (see Evans et al, 2009 ; Crossland et al, 2018 ; Monds et al, 2021 ; Hagsand et al, 2022a , b ; Pettersson et al, 2022 ). As the first novel study on interrogations concerning low-stakes crimes related to alcohol and/or drugs, the present study provides useful information about current Swedish interrogation practices and areas for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of national policy guidelines in some countries results in different interrogation practices across police stations and investigators within stations. In the case of drug- and alcohol-related crimes, police officers must use their own judgment when deciding when, how and where to interrogate/interview sober, alcohol- or drug-intoxicated suspects, witnesses and victims (see Evans et al, 2009 ; Crossland et al, 2018 ; Hagsand et al, 2022a , b ; Pettersson et al, 2022 ). Sweden currently differs from the neighboring Norway, as well as United Kingdom, in that there is no clear national policy for how interrogations should be carried out by the police.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the current absence of a national policy on interrogation and investigative interview methods, samples of Swedish police officers recently self‐reported in surveys that they use their own subjective judgement when deciding on when, how, and where to interrogate suspects, witnesses, and victims of crimes (Hagsand, Evans, Pettersson & Schreiber Compo, 2022; Hagsand, Pettersson, Evans & Schreiber Compo, 2022; Pettersson, Bergquist & Hagsand, 2022). Further, a Scandinavian police survey on interrogations with suspects of child sexual abuse showed that the type of emotion interrogators experienced during an interview affected which interrogation tactics they used (Magnusson, Joleby, Luke, Ask & Lefsaker Sakrisvold, 2021).…”
Section: Current Interrogation Practice In Swedenmentioning
confidence: 99%